Out with the sleaze, in with the ease: Insufficient for entrepreneurial development? - Wim Naudé (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
Improved governance and lower start-up costs may not be sufficient for encouraging the type of entrepreneurship that matters for economic growth. Using panel data on 60 countries spanning the period 2003-07 this paper establishes that (i) opportunitymotivated entrepreneurship (as opposed to necessity-motivated entrepreneurship) drives economic growth; (ii) governance and the start-up costs are not significant determinants of opportunity entrepreneurship; and (iii) better governance leads to higher economic growth. This implies that better governance and lower start-up costs, widely advocated as measures to promote entrepreneurship in developing countries, may not in fact be enough. Indeed, despite poorer governance and higher start-up costs, rates of opportunity-motivated entrepreneurship are higher in developing countries. Second, better governance can lead to better growth through reducing the impact of destructive entrepreneurship (including rent-seeking), even though this may not result in a reallocation of effort from destructive towards opportunity-motivated entrepreneurship. The paper concludes by discussing whether these results call in question the popular belief that a lack of opportunity-motivated entrepreneurship constrains developing country growth, and whether there is justification for more proactive government support for entrepreneurship.
Keywords: M13; L26; O10; O14; 330; entrepreneurship; development; institutions; Entrepreneurship-Ansatz; Unternehmensentwicklung; Wirtschaftswachstum; Welt